Genetic Variation Between and Within Three Varieties of Domesticated Tiger Barb (Puntius Tetrazona) Using Rapd Markers - Ariffin, Nur Asma (1999)
Tiger barb (Puntius tetrazona) is one of the popular ornamental fish species cultured and is a significant component of the aquarium fish industry in Malaysia This study was conducted to assess genetic variation between and within three varieties of domesticated Tiger barb using random amplified polymorphic DNA (RAPD) markers. Genetic markers are important to selective breeding programmes and as a supportive research in order to minimise incorrect identification and stock contamination. Fifty random individuals of each variety (normal, green and yellow) were obtained from Perak and Johor, which are the main producers of Tiger barb in